The Influence of Promotion via LINE Messenger on the Attitude of Starbucks’ LINE Official Account Followers - Santi Delliana; Vira Dessy Arisandi (Bina Nusantara University, 2020)
The research aimed to determine the effect of promotion through persuasive messages via LINE messenger applications on the attitude of Starbucks’ LINE official account followers. The analytical research applied the S-R (Stimulus-Responses) theory with quantitative approaches and survey methods by distributing questionnaires in analytical to 400 respondents, who are followers of Starbucks’ LINE official account. The research uses sociopsychological tradition focusing on individual social behavior, personal effects, perception, cognition, personality and traits. Research findings were based on the answers of respondents who strongly agree on cognitive, contextual, and affective indicators. The research comes up with results indicating that there is a strong influence of promotion via LINE messenger on the attitude of Starbucks’ LINE followers, where the magnitude is positive. The results find that customers receive Starbucks’ promotion messages with positive attitudes and feedbacks as well. It is suggested that future research consider to determine the occurrence of stages of customers’ purchase decision.